2020
DOI: 10.1021/acs.energyfuels.0c01921
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Perturbation Correlation Infrared Spectroscopy for Probing Pyrolysis of Biomass: Fundamentals, Applications, and Mechanistic Understanding

Abstract: Pyrolysis is a promising technology that can efficiently convert biomass into gas, liquid, and solid fuels. Elucidating the biomass pyrolysis reaction mechanism is essential for the effective biomass utilization. However, the biomass components and structure are very complex, which complicates the investigation of biomass pyrolysis using traditional approaches. Two-dimensional perturbation correlation infrared spectroscopy (2D-PCIS) represents a new analytical method for visualizing the raw Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 114 publications
1
10
0
Order By: Relevance
“…61 Previous studies also reported that the functional group chemistry of biomass was dominated by bonded OH and R−CH n to be dominated by free −OH and RCH n groups at approximately 300−350 °C. 31,34 Additionally, the depolymerization/cracking reactions of unstable compounds in cellulose and the ether-bridge structures in lignin could result in the formation of large aromatic rings in residues and small-chain VOCs of aldehydes, ketones, and cyclopentanones. 32,61 Kibet et al also found that the gaseous acetones released from lignin achieved a maximum concentration at ∼350 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…61 Previous studies also reported that the functional group chemistry of biomass was dominated by bonded OH and R−CH n to be dominated by free −OH and RCH n groups at approximately 300−350 °C. 31,34 Additionally, the depolymerization/cracking reactions of unstable compounds in cellulose and the ether-bridge structures in lignin could result in the formation of large aromatic rings in residues and small-chain VOCs of aldehydes, ketones, and cyclopentanones. 32,61 Kibet et al also found that the gaseous acetones released from lignin achieved a maximum concentration at ∼350 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…61,76 This result was in good agreement with the heterosynchronous gas−solid correlations and the reported gaseous chain/cyclic oxygen-containing molecules released from hemicellulose dehydration at 200−300 °C. 34 Subsequently, through ring opening and fragmentation, the oxygen bridge bond, pyran ring C−O, aliphatic −CH, and −COOH groups on the residual aromatic branches could result in the formation of gaseous alcohols/phenols/esters. Previous studies supported this result and reported that the rupture of aromatic methoxy and aliphatic −CH 2 OH groups in alkyl side chains in lignin provoked the release of gaseous phenolic/alcohols (e.g., methanol) below 300 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations